If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + 5 = 2 Reorder the terms: 5 + a = 2 Solving 5 + a = 2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + a = 2 + -5 Combine like terms: 5 + -5 = 0 0 + a = 2 + -5 a = 2 + -5 Combine like terms: 2 + -5 = -3 a = -3 Simplifying a = -3
| z+2.5=6.3 | | 18-5(x+1)=13 | | 5x+10=91-4 | | 3X+7=25-X | | 1/2x+x+x+(x+5)=100 | | -Y^2-10Y+19=0 | | R/6+2/3=9 | | 7x+7y=1 | | 3x-0.5=1.5 | | y+x+(x+5)=100 | | (2x-5+8z)-3(6x-4y+10z)= | | 77-3x=33x+21 | | 2x+0.5=1 | | 4x+2/5=6 | | 4x/5=8/9 | | -6x^2+216=0 | | 16t^2-16t+80=0 | | x*8+25=2x+39 | | 2(2y+1)+5(y+2)=30 | | (x+3)^2=5/20 | | 2x-25=5 | | 5x-7=4-3x | | 5x-10=7-3x | | 4p-4q+2q+2p= | | 4p-4q+2q-2p= | | 5a+8b-8a+7ab-10b= | | y=1/x-4 | | -3x+9y=-6 | | 10x+700=15x | | (x+8)(3x-10)+8x^2-(5+x)(2x-3)= | | -4x+9=3x-6 | | 3x+7=6x+8 |